Pseudomonas arcuscaelestis sp. nov., isolated from rainbow trout and water. Issue 7 (9th July 2021) - Mulet, Magdalena; Duman, Muhammed; Altun, Soner; Saticioglu, Izzet Burcin; Gomila, Margarita; Matthijs, Sandra; Lalucat, Jorge; García-Valdés, Elena
Abstract : Cells of strains P66 T, V1 and W15Feb18 are Gram-stain-negative short rods and motile by one polar flagellum. Strain P66 T was isolated from rainbow trout ( Oncorhynchus mykiss ) cultivated at a fish farm in Turkey. Strain V1 was isolated from sand of an intertidal shore on the Galicia coast in Spain and strain W15Feb18 was isolated from water collected at the Woluwe River in Belgium. Based on 16S rRNA sequence similarity values, the strains were grouped under the genus Pseudomonas and the Pseudomonas putida phylogenetic group of species. The DNA G+C content ranged from 58.5 to 58.9 mol%. The strains were characterized phenotypically by the API 20NE and Biolog GEN III tests, and chemotaxonomically by their whole-cell MALDI-TOF MS protein profiles and fatty acid contents. The absence of the hydrolysis of gelatin and the assimilation of arabinose, mannose and mannitol differentiated these strains from the closest species, Pseudomonas alkylphenolica . The major fatty acid components were C16:0 (29.91–31.68 %) and summed feature 3 (36.44–37.55 %). Multilocus sequence analysis with four and 83 housekeeping gene sequences and a core proteome analysis showed that these strains formed a phylogenetic cluster in the P. putida group of species. Genome comparisons by the average nucleotide identity based on blast and the Genome-to-Genome Distance Calculator demonstrated that the three strains belonged to the same genomic species and were distant from any known species, with similarity values lower than the thresholds established for species in the genus Pseudomonas . These data permitted us to conclude that strains P66 T, V1 and W15Feb18 belong to a novel species in the genus Pseudomonas, for which the name Pseudomonas arcuscaelestis sp. nov. is proposed. The type strain is P66 T (=CECT 30176 T =CCUG 74872 T ). The other strains have been deposited in the CECT with the corresponding collection numbers: V1 (=CECT 30356) and W15Feb18 (=CECT 30355).